The role of the discipline «Foreign language» in developing a professional communicative identity in the system of higher education - Lushchynskaya, Volha V.; Savich, Alena V. (Journal of the Belarusian State University. Journalism, 2019)
The article considers issues related to the development of the professional communicative (discourse) identity in the system of higher education using foreign language as a means of achieving this goal. Competences (a system of knowledge, skills  and abilities) necessary for the future specialists in their professional activity are specified and edited. Methodological bases  of the discourse approach are defined and its foundations as applied to teaching foreign languages in the system of higher  education are described. The focus is made on the necessity to consider the key category of «communicative situation», being  treated as a holistic unity of its linguistic and extralinguistic features, while designing the process and content of teaching  students to interact in a foreign language environment.
Keywords: competence approach; professional communicative (discourse) identity; communicative competence; discourse approach; discourse skills; oral and written communication in a foreign language